DETERMINATION OF CARCINOGENIC POLYCYCLIC AROMATIC HYDROCARBONS IN AIR SAMPLES IN IRBID, NORTH JORDAN - Muhammad Barzani, Gasim; Azman, Azid; Abdul Rahman, Hassan (2018)
Air samples were collected at an urban site and a rural (BERQESH) site during February (2017) until March (2017) to determine concentrations of polycyclic aromatic hydrocarbons (PAHs) in Air. The extraction process was done by using Soxhlet apparatus and methylene chloride as solvent. The sample clean up step is performed by solid phase extraction. The analysis of PAHs samples are carried out by GC/MS. Low molecular weight PAHs dominated in all samples such as acenaphthylene, fluorene and anthracene, while high molecular weight PAHs was not detected. The total mean PAHs concentration in summer in Rural Area (92ng/m 3 ) is higher than that in winter (46 ng/m 3 ). In addition, PAHs total mean concentration in the day time is higher than that in the night time. The total mean PAHs concentration in summer in Urban Area (124 ng/m 3 ) is higher than that in winter (75 ng/m 3 ).